Lives in ruins [compact disc, unabridged] : archaeologists and the seductive lure of human rubble - Johnson, Marilyn, 1954- (Tantor Audio, 2014)
The author of The Dead Beat and This Book is Overdue! turns her piercing eye and charming wit to the real-life avatars of Indiana Jones-the archaeologists who sort through the muck and mire of swamps, ancient landfills, volcanic islands, and other dirty places to reclaim history for us all.